Labour Productivity for External Works Construction: Case Study in Kluang, Johor - Mazlan, Wan Muhammad Idlan Danish; Yaman, Siti Khalijah (Journal of Structural Monitoring and Built Environment, 2025)
The construction industry in Malaysia faces persistent productivity challenges, including a shortage of skilled labor, high worker turnover, and equipment inefficiencies, which lead to project delays, reduced output, and compromised quality. Accurate labor productivity data is critical for optimizing workforce allocation, scheduling, and resource utilization; however, the lack of such data hinders effective decision-making. This study evaluates labor productivity in external infrastructure projects, focusing on roadworks, drainage systems, and sewerage systems in Kluang, Johor. Using direct measurement methods, productivity rates across various tasks were assessed, and the impacts of factors such as site conditions, weather disruptions, and workforce experience were analyzed. The findings highlight the positive influence of skilled labor and appropriate equipment on productivity, while adverse weather and site-specific challenges were identified as significant contributors to inefficiencies. Effective site management was found to be a key determinant of improved labor productivity and adherence to project timelines. Recommendations include workforce training, enhanced site management practices, and optimized labor allocation to mitigate delays, improve productivity, and deliver competitive project outcomes.